The low-FODMAP diet and the gluten-free diet in the management of functional abdominal bloating and distension - Pessarelli, Tommaso; Sorge, Andrea; Elli, Luca; Costantino, Andrea (Frontiers in Nutrition, 2022)
This review summarizes current knowledge on the role of low-FODMAP diet and gluten-free diet in functional abdominal bloating and distension, an emerging disorder of gut-brain interaction characterized by remarkable costs for healthcare systems and a significant impact on the patient’s quality of life. Ingested food plays a key role in the pathophysiology of disorders of gut-brain interaction as up to 84% of patients with irritable bowel syndrome (IBS) report food-triggered symptoms. Potential pathogenetic mechanisms of food-related symptoms in these patients are discussed, focusing on bloating and abdominal distension. These mechanisms provide the rationale for dietary treatment in patients with functional abdominal bloating and distension. The role of fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) and gluten in functional abdominal bloating and distension is examined. Current literature evaluating the efficacy of the low-FODMAP diet and the gluten-free diet in abdominal bloating and distension is analyzed. Available evidence originates mainly from studies on patients with IBS, since clinical studies on selected cohorts of patients with only functional abdominal bloating and distension have been missing to date. Promising evidence on the potential efficacy of the low-FODMAP diet in functional abdominal bloating and distension is provided by the reduction of the bloating observed in patients with IBS. Regarding the gluten-free diet, there is insufficient evidence to recommend it to reduce bloating and abdominal distension. In conclusion, this review asserts the need for a close collaboration with experts in nutrition to optimize the management of these patients and reduce the risks associated with elimination diets.